Art Funds (Raton, NM Raton Range, 1995)
Article about the council receiving donations from US West Communications, Inc. and from Sunwest Bank.
Newspaper article + 2 Photographs 1) Frank Reed and Marilyn Donati 2) Marilyn Donati and Terri Segotta
Master list item #: 106
File location is in the Raton file Cabinet
Keywords: Donati, Marilyn -- Art and Humanities Council Director; Reed, Frank -- New Mexico Community Affairs Manager for US West Communications, Inc; Segotta, Terri -- Sunwest Bank Representative; Us West Communications, Inc. -- Sponsor; Sunwest Bank -- Sponsor; Old Pass Gallery; Missoula Children's Theater; Performance Donations; Program Donations; Children's Art; Children's Plays; Raton, New Mexico